RANCANG BANGUN MESIN PENGUPAS KULIT BAWANG MERAH - Shafira Nindhia Fira; Anugerah Putra R; Bayu Prasetya; Husman Husman; Adhe Anggry (Prosiding Seminar Nasional Inovasi Teknologi Terapan, 2022)
In the Sungailiat area, there are many SME (small and medium enterprises) culinary types, one of which is processed fried onions. Yuliana's mother is the owner of a fried onion business called "Bagor BTN". Every day 10 kg of shallots are peeled to produce fried onions, even up to 60 kg on holidays. To peel 10 kg of red onions takes about 3-4 hours. So far, the red onion peeling process is still done manually, namely by peeling it using a knife. The purpose of the design of this shallot skin peeler machine is to be able to peel 80% of the onion skin with a capacity of 10 kg/hour by using a peeler and a rubber peeler. The research method used is Method 3E (ECO-EFE-EFI) according to Dieter & Schmidt. The test results of the onion peeler machine that have been carried out show that 90% of red onions are peeled as much as 3 kg in one process within 10 minutes, so that in 1 hour they are able to peel 18 kg/hour onions.